Health Education Media to Increase Vegetable and Fruit Consumption in School-Aged Children - Widyana Lakshmi Puspita; Khayan; Suaebah; Bagus Muhammad Ihsan; Muhammad Ifham Hanif (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The lack of regulatory substances from fruits and vegetables is related to individual factors. Aims: The purpose of this study is to determine the effect of using educational media, lift-the-flap books, and leaflets on increasing knowledge, attitudes, parental support, and consumption of vegetables and fruit in elementary school children. Methods: This type of research was a quasi-experiment with a pre-and post-design approach to see the causal relationship between before and after counseling intervention with lift-the-flap book and leaflet media on increasing knowledge, attitudes, parental support, and consumption of vegetables and fruits in school-age children. Measuring knowledge scores, attitudes, and parental support was done using a Likert scale, and vegetable and fruit consumption using a 2x24-hour recall. Statistical analysis was conducted using the Test correlation test with a 95% confidence level (α = 5%). Results: Based on the research, it can be seen that using the lift-the-flap books and leaflet media can increase knowledge, attitudes, parental support, and consumption of vegetables and fruit compared to before using the media in elementary school children Pontianak. Conclusion: Lift-the-flap books are more effective in increasing knowledge, attitudes, parental support, and consumption of vegetables and fruits than leaflets.